Coated modified positive electrode material, preparation method thereof and battery
By growing B2O3 on the surface of the nickel-cobalt-manganese ternary positive electrode material and modifying the CoPcCl layer, the structural damage caused by the contact between the positive electrode material and the electrolyte is solved, and the circulation performance and reaction rate of the battery are improved.
Patent Information
- Application Number
- CN202411390128.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-24
AI Technical Summary
The nickel-cobalt-manganese ternary cathode material comes into contact with the electrolyte during the charging and discharging of lithium-ion batteries, resulting in structural damage and affecting the battery's cycle life, rate performance and safety performance.
Using a multi-component coating method, the B2O3 layer is first grown on the surface of the positive electrode material, and then the CoPcCl layer is modified to enhance structural stability and accelerate ion and electron transport.
The structural stability and cycling performance of the positive electrode material are improved, and the cycling performance and reaction rate of the battery are enhanced.
Smart Images

Figure CN119181788A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to coating modification of positive electrode materials. Background Art
[0002] Positive electrode materials are an important component of lithium-ion batteries. The performance of positive electrode materials greatly affects the charge and discharge performance of lithium-ion batteries assembled from them. Nickel-cobalt-manganese ternary positive electrode materials have the advantages of high specific capacity, low cost and environmental friendliness due to the synergistic effect between transition metals. They are widely used in portable devices, electric vehicles and energy storage fields. However, during the charge and discharge process of the battery, the ternary positive electrode material is in contact with the electrolyte and is in a thermodynamically unstable state. The delithiation positive electrode material is in direct contact with the electrolyte and is easy to react with the electrolyte, causing some metal ions in the positive electrode material to dissolve into the electrolyte, destroying the structure of the positive electrode material and affecting the battery's cycle life, rate performance and safety performance. It is currently a common practice to coat and modify the positive electrode material to improve the performance of the positive electrode material. It is crucial to select suitable coating materials and coating processes. Summary of the invention
[0003] The main purpose of the present invention is to provide a coated modified positive electrode material and a preparation method thereof.
[0004] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0005] First, the present invention provides a coated modified positive electrode material, comprising a substrate and a first coating layer and a second coating layer sequentially distributed from the core to the surface of the substrate; the material of the first coating layer is B2O3; the material of the second coating layer is CoPcCl.
[0006] In a further preferred embodiment, the chemical formula of the matrix is LiNi x Co y Mn z O2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1.
[0007] Secondly, the present invention provides a method for preparing a coated modified positive electrode material, comprising the following steps: Step S1, adding the positive electrode material to an ethanol solution of H3BO3, stirring, evaporating, and drying to obtain a powder; the powder is pyrolyzed in an inert atmosphere to obtain a composite material; the chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1; Step S2, sintering the composite material and the mixed material after grinding and mixing with CoPcCl to obtain a coated modified positive electrode material.
[0008] In a further preferred embodiment, the concentration of H3BO3 in the H3BO3 ethanol solution is 0.5-1.5 g / L.
[0009] In a further preferred embodiment, the solid-liquid ratio of the positive electrode material to the ethanol solution of H3BO3 is 4-6 g:100 mL.
[0010] In a further preferred embodiment, the evaporation to dryness is carried out by heating in a water bath or an oil bath.
[0011] In a further preferred embodiment, the pyrolysis temperature is 600-1000°C.
[0012] In a further preferred embodiment, the mass ratio of the composite material to CoPcCl is 100:0.5-2.
[0013] In a further preferred embodiment, the sintering temperature is 700-1000° C. and the sintering time is 2-8 hours.
[0014] In a further preferred embodiment, CoPcCl is prepared by the following method: dissolving phthalonitrile and CoCl2 in 1,2-dichlorobenzene at a molar ratio of 4:1, stirring and heating to obtain a reaction product; adding ether to the reaction product, mixing well and filtering to obtain CoPcCl.
[0015] Preferably, the solid-liquid ratio of CoCl2 to 1,2-dichlorobenzene is 1-2g:50mL.
[0016] Preferably, the heating temperature is 180-220°C.
[0017] Based on the same inventive concept, the present invention provides a battery comprising the aforementioned coated and modified positive electrode material.
[0018] Coating strategy is a common method for modifying positive electrode materials, and different coating materials usually play different roles. The present invention uses a multi-component coating method to modify the positive electrode material. First, B2O3 is grown in situ on the surface of the positive electrode material to increase the structural stability of the positive electrode material while increasing the capacity; then a layer of CoPcCl is modified. Since CoPcCl has a strong catalytic effect, it can accelerate the transmission of ions and electrons, has high electrochemical activity for lithium ions, and is beneficial to the deintercalation of lithium ions, which can further improve the structural stability during the cycle, enhance the reaction rate, and improve the cycle performance.
[0019] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The positive electrode material is modified by a multi-component coating method, and the structural advantages of the coating are utilized to enhance the structural stability of the positive electrode material, resist structural changes during the charge and discharge process, and improve the cycle performance of the battery.
[0020] The coating process of the invention is simple and easy to operate and can be applied in large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 LiNi 0.9 Co 0.05 Mn 0.05 SEM image of O2.
[0022] Figure 2 This is the SEM image of material A in Example 1.
[0023] Figure 3 This is the SEM image of the coated and modified positive electrode material in Example 1.
[0024] Figure 4 This is the cycle performance diagram of the battery. DETAILED DESCRIPTION
[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0026] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0028] Example 1 Step (1): 5g of positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 and 0.09g H3BO3 were added to 100mL ethanol solution, stirred for 3h to fully disperse, then placed in an oil bath and stirred at 100℃ to evaporate to dryness, the evaporated product was moved into an oven and dried at 120℃ for 6h to obtain powder; Step (2): The obtained powder was pyrolyzed at 800°C for 1 h in an Ar atmosphere to obtain material A; Step (3): dissolving 3.95 g of phthalonitrile and 1 g of CoCl2 in 50 mL of 1,2-dichlorobenzene, and heating with stirring at 200°C for 12 hours to obtain a reaction product; adding ether to the reaction product, shaking well, filtering, and washing the solid phase with ether to obtain CoPcCl; Step (4): 5 g of material A and 0.05 g of CoPcCl were ground and mixed, and then annealed at 900 °C for 6 h in an air atmosphere to obtain a coated modified positive electrode material.
[0029] Figure 1 LiNi 0.9 Co 0.05 Mn 0.05 SEM image of O2, the surface is smooth; Figure 2 This is the SEM image of material A. It can be seen that there are fine particles on the surface and they are evenly distributed.
[0030] Figure 3 This is the SEM image of the coated modified positive electrode material. It can be seen that the surface particles become larger and more obvious.
[0031] Comparative Example 1 Step (1): 5g of positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 and 0.09g H3BO3 were added to 100mL ethanol solution, stirred for 3h to fully disperse, then placed in an oil bath and stirred at 100℃ to evaporate to dryness, the evaporated product was moved into an oven and dried at 120℃ for 6h to obtain powder; Step (2): The obtained powder is pyrolyzed at 800° C. for 1 h in an Ar atmosphere to obtain a coated modified positive electrode material.
[0032] Comparative Example 2 Step (1): 3.95 g of phthalonitrile and 1 g of CoCl2 are dissolved in 50 mL of 1,2-dichlorobenzene, and heated with stirring at 200°C for 12 hours to obtain a reaction product; ether is added to the reaction product, shaken, filtered, and the solid phase is washed with ether to obtain CoPcCl; Step (2): 5g of positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 was ground and mixed with 0.05 g CoPcCl, and then annealed at 900 °C for 6 h in an air atmosphere to obtain a coated modified positive electrode material.
[0033] Example 2 Step (1): 8g of positive electrode material LiNi 0.8 Co 0.1 Mn 0.1O2 and 0.2g H3BO3 were added to 200 mL ethanol solution, stirred for 3h to fully disperse, then placed in an oil bath and stirred at 100℃ to evaporate to dryness, the evaporated product was moved into an oven and dried at 120℃ for 6h to obtain powder; Step (2): The obtained powder was pyrolyzed at 600°C for 2 h in an Ar atmosphere to obtain material A; Step (3): dissolving 3.95 g of phthalonitrile and 1 g of CoCl2 in 25 mL of 1,2-dichlorobenzene, and heating with stirring at 180°C for 12 hours to obtain a reaction product; adding ether to the reaction product, shaking well, filtering, and washing the solid phase with ether to obtain CoPcCl; Step (4): 5 g of material A and 0.025 g of CoPcCl were ground and mixed, and then annealed at 700 °C for 2 h in an air atmosphere to obtain a coated modified positive electrode material.
[0034] Example 3 Step (1): 6g of positive electrode material LiNi 0.85 Co 0.05 Mn 0.1 O2 and 0.05g H3BO3 were added to 100 mL ethanol solution, stirred for 3h to fully disperse, then placed in an oil bath and stirred at 100℃ to evaporate to dryness, the evaporated product was moved into an oven and dried at 120℃ for 6h to obtain a powder; Step (2): The obtained powder was pyrolyzed at 1000°C for 1 h in an Ar atmosphere to obtain material A; Step (3): dissolving 3.95 g of phthalonitrile and 1 g of CoCl2 in 50 mL of 1,2-dichlorobenzene, and heating with stirring at 220°C for 12 hours to obtain a reaction product; adding ether to the reaction product, shaking well, filtering, and washing the solid phase with ether to obtain CoPcCl; Step (4): 5 g of material A and 0.1 g of CoPcCl were ground and mixed, and then annealed at 1000° C. for 2 h in an air atmosphere to obtain a coated modified positive electrode material.
[0035] Example 4 Step (1): 12g of positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 and 0.3g H3BO3 were added to 200mL ethanol solution, stirred for 3h to fully disperse, then placed in an oil bath and stirred at 100℃ to evaporate to dryness, the evaporated product was moved into an oven and dried at 120℃ for 6h to obtain powder; Step (2): The obtained powder was pyrolyzed at 700°C for 2h under Ar atmosphere to obtain material A; Step (3): dissolving 3.95 g of phthalonitrile and 1 g of CoCl2 in 50 mL of 1,2-dichlorobenzene, and stirring and heating at 190°C for 12 hours to obtain a reaction product; adding ether to the reaction product, shaking well, filtering, and washing the solid phase with ether to obtain CoPcCl; Step (4): 5 g of material A and 0.075 g of CoPcCl were ground and mixed, and then annealed at 900 °C for 2 h in an air atmosphere to obtain a coated modified positive electrode material.
[0036] The coated modified positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-2 and the positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2 is assembled into a battery in the following way: Positive electrode material: Conductive graphite: PVDF was weighed and ground according to a mass ratio of 8:1:1, dissolved in an appropriate amount of N-methylpyrrolidone (NMP) and stirred evenly to form a slurry, and then the slurry was coated on the current collector aluminum foil, dried at 90°C for 12 hours in a blast dryer, and punched into a disc electrode with a diameter of 12 mm. The disc electrode was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the lithium ion secondary electrolyte LB-037 (1M LiPF6in DEC:EC:EMC=1:1:1 Vol%) was used as the electrolyte, and Celgard2325 was used as the separator. The LIR2032 button battery was assembled in the glove box according to the assembly sequence of the button battery.
[0037] Test the electrical performance of the battery: In a constant temperature box at 25℃, charge the battery at a constant current of 0.1C to a voltage of 4.3V, then charge it at a constant voltage of 0.01C, and then discharge it at 0.1C to 3V. Repeat this cycle twice. Then charge the battery at a constant current of 0.5C to a voltage of 4.3V, then charge it at a constant voltage of 0.5C, and then discharge it at 0.5C to 3V. Record the charge and discharge capacity.
[0038] The test results are as follows Figure 4 shown.
[0039] The battery assembled with the coated modified positive electrode materials obtained in Comparative Example 1 and Comparative Example 2 and the LiNi 0.9 Co 0.05 Mn 0.05 Compared with the performance of batteries assembled with O2, coating the positive electrode material with B2O3 or CoPcCl can improve the initial specific capacity and cycle performance of the battery.
[0040] By comparing the initial specific capacity of the battery assembled with the coated modified positive electrode material obtained in Example 1, Comparative Example 1, and Comparative Example 2, it is found that the initial specific capacity of the battery assembled with the positive electrode material modified by coating with B2O3 and CoPcCl in Example 1 is higher than the initial specific capacity of the battery assembled with the single-phase coated modified positive electrode material obtained in Comparative Example 1 and Comparative Example 2; the battery assembled with the coated modified positive electrode material obtained in Example 1 has better cycle performance than the battery assembled with the coated modified positive electrode material obtained in Comparative Example 1 and Comparative Example 2, and the cycle performance is quite different. This may be due to: B2O3 is grown in situ on the surface of the positive electrode material, increasing the structural stability of the positive electrode material while increasing the capacity; and then a layer of CoPcCl is modified. Since CoPcCl has a strong catalytic effect, it can accelerate the transmission of ions and electrons, has advantages such as high electrochemical activity for lithium ions, is conducive to the deintercalation of lithium ions, and can further improve the structural stability during the cycle, enhance the reaction rate, and improve the cycle performance.
[0041] The battery assembled with the coated modified positive electrode material obtained in Examples 2-4 also has excellent cycle performance.
[0042] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coated modified positive electrode material, characterized in that: It comprises a substrate and a first coating layer and a second coating layer which are sequentially distributed along the direction from the core to the surface of the substrate; the material of the first coating layer is B2O3; the material of the second coating layer is CoPcCl.
2. The coated modified positive electrode material according to claim 1, characterized in that: The general chemical formula of the matrix is LiNi x Co y Mn z O2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1.
3. A method for preparing a coated modified positive electrode material, characterized in that: The following steps are involved: Step S1, adding the positive electrode material to an ethanol solution of H3BO3, stirring, evaporating, and drying to obtain a powder; the powder is pyrolyzed in an inert atmosphere to obtain a composite material; the chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z=1; Step S2, sintering the composite material and the mixed material after grinding and mixing with CoPcCl to obtain a coated modified positive electrode material.
4. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The concentration of H3BO3 in the H3BO3 ethanol solution is 0.5-1.5 g / L; the solid-liquid ratio of the positive electrode material to the H3BO3 ethanol solution is 4-6 g:100 mL.
5. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The pyrolysis temperature is 600-1000°C.
6. The method for preparing the coated modified positive electrode material according to claim 3, characterized in that: The mass ratio of the composite material to CoPcCl is 100:0.5-2; the sintering temperature is 700-1000°C; and the sintering time is 2-8h.
7. The method for preparing a coated and modified positive electrode material according to any one of claims 3 to 6, characterized in that: CoPcCl is prepared by the following method: dissolving phthalonitrile and CoCl2 in 1,2-dichlorobenzene at a molar ratio of 4:1, stirring and heating to obtain a reaction product; adding ether to the reaction product, mixing well and filtering to obtain CoPcCl.
8. The method for preparing the coated modified positive electrode material according to claim 7, characterized in that: The solid-liquid ratio of the CoCl2 to 1,2-dichlorobenzene is 1~2g:50mL.
9. The method for preparing the coated modified positive electrode material according to claim 7, characterized in that: The heating temperature is 180~220℃.
10. A battery, characterized in that: It includes the coated and modified positive electrode material according to claim 1 or 2, or the coated and modified positive electrode material prepared by the preparation method according to any one of claims 3 to 9.
Citation Information
Cited By
Positive electrode material and preparation method and application thereof
CN119695127A
